Macroautophagy: The key ingredient to a healthy diet? - Hannigan, Adrienne M. (2009)
Dietary compounds can influence the risk of cancer and other diseases through diverse mechanisms which include the activation or inhibition of macroautophagy. Macroautophagy is a catabolic process for the lysosomal degradation and recycling of cytoplasmic constituents which has been implicated in several pathologies, including cancer and neurodegeneration. In some instances, macroautophagy acts to suppress tumor formation and neural degeneration. Thus, it may be feasible to design diets, supplements or therapeutics that can alter the level of macroautophagy within cells to prevent or treat disease. While critical questions still need to be answered before we can safely and effectively implement such a strategy, we provide here a review of the literature regarding dietary constituents that have a demonstrated macroautophagy-modulating function.